1997
DOI: 10.3748/wjg.v3.i4.266
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and experimental studies on stomach carcinoma treated with Yangwei Kangliu granules

Abstract: The anti-cancer mechanism of YWKL granules may involve enhancement of RBC immunity and of T lymphocyte immune function, which is supported by the finding of RBC immune function being correlated with T lymphocyte immune function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…A herb medicine formula "Yang Wei Kang Liu" (YWKLF), consisting of six herbs, has been used for a number of years in traditional medicine to promote circulation and human body resistance to pathogens and cancer. Preliminary clinical studies have shown that YWKLF modulates immune function, improves the quality of life, and prolongs survival time of cancer patients [3]. However, the molecular mechanisms underlying the anti-cancer effect of YWKLF are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…A herb medicine formula "Yang Wei Kang Liu" (YWKLF), consisting of six herbs, has been used for a number of years in traditional medicine to promote circulation and human body resistance to pathogens and cancer. Preliminary clinical studies have shown that YWKLF modulates immune function, improves the quality of life, and prolongs survival time of cancer patients [3]. However, the molecular mechanisms underlying the anti-cancer effect of YWKLF are poorly understood.…”
Section: Introductionmentioning
confidence: 99%